Depletion of B cells rejuvenates the peripheral B‐cell compartment but is insufficient to restore immune competence in aging. Issue 4 (6th May 2019) - Avivi, Irit; Zisman‐Rozen, Simona; Naor, Shulamit; Dai, Isabelle; Benhamou, David; Shahaf, Gitit; Tabibian‐Keissar, Hilla; Rosenthal, Noemie; Rakovsky, Aviya; Hanna, Ammuri; Shechter, Arik; Peled, Eli; et al.
Abstract: Aging is associated with increasing prevalence and severity of infections caused by a decline in bone marrow (BM) lymphopoiesis and reduced B‐cell repertoire diversity. The current study proposes a strategy to enhance immune responsiveness in aged mice and humans, through rejuvenation of the B lineage upon B‐cell depletion. We used hCD20Tg mice to deplete peripheral B cells in old and young mice, analyzing B‐cell subsets, repertoire and cellular functions in vitro, and immune responsiveness in vivo. Additionally, elderly patients, previously treated with rituximab healthy elderly and young individuals, were vaccinated against hepatitis B (HBV) after undergoing a detailed analysis for B‐cell compartments. B‐cell depletion in old mice resulted in rejuvenated B‐cell population that was derived from de novo synthesis in the bone marrow. The rejuvenated B cells exhibited a "young"‐like repertoire and cellular responsiveness to immune stimuli in vitro. Yet, mice treated with B‐cell depletion did not mount enhanced antibody responses to immunization in vivo, nor did they survive longer than control mice in "dirty" environment. Consistent with these results, peripheral B cells from elderly depleted patients showed a "young"‐like repertoire, population dynamics, and cellular responsiveness to stimulus. Nevertheless, the response rate to HBV vaccination was similar between elderly depleted and nondepleted subjects, although antibody titers were higher in depleted patients. This study proposes a proof of principle to rejuvenate the peripheral B‐cell compartment in aging, through B‐cell depletion. Further studies are warranted in order to apply this approach for enhancing humoral immune responsiveness among the elderly population. Abstract : A physiologically applicable B‐cell rejuvenation strategy proof of concept. A rejuvenated immune system, expanding the naïve B‐cell compartment, would improve response to new pathogens, thereby may decrease the risk of infections, an objective that is often unachieved in elderly subjects, and may increase response to new immunogenic stimuli such as vaccines.